Tramadol Induced Adrenal Insufficiency: Histological, Immunohistochemical, Ultrastructural, and Biochemical Genetic Experimental Study - Shereen Abdelhakim Abdelaleem; Osama A. Hassan; Rasha F. Ahmed; Nagwa M. Zenhom; Rehab A. Rifaai; Nashwa F. El-Tahawy (Journal of Toxicology)
Tramadol is a synthetic, centrally acting analgesic. It is the most consumed narcotic drug that is prescribed in the world. Tramadol abuse has dramatically increased in Egypt. Long term use of tramadol can induce endocrinopathy. So, the aim of this study was to analyze the adrenal insufficiency induced by long term use of tramadol in experimental animals and also to assess its withdrawal effects through histopathological and biochemical genetic study. Forty male albino rats were used in this study. The rats were divided into 4 groups (control group, tramadol-treated group, and withdrawal groups). Tramadol was given to albino rats at a dose of 80 mg/kg body weight for 3 months and after withdrawal periods (7–15 days) rats were sacrificed. Long term use of tramadol induced severe histopathological changes in adrenal glands. Tramadol decreased the levels of serum cortisol and DHEAS hormones. In addition, it increased the level of adrenal MDA and decreased the genetic expression of glutathione peroxidase and thioredoxin reductase in adrenal gland tissues. All these changes started to return to normal after withdrawal of tramadol. Thus, it was confirmed that long term use of tramadol can induce severe adrenal insufficiency.